The bear [compact disc, unabridged] : a novel - Cameron, Claire, 1973- (Dreamscape Media, Llc, 2014)
Told from the point of view of a six-year-old child, this is the story of Anna and her little brother, Stick, two young children forced to fend for themselves in Algonquin Park after a black bear attacks their parents. A gripping and mesmerizing exploration of the child psyche, this is a survival story unlike any other, and one that asks what it takes to survive in the wilderness and what happens when predation comes from within.